Manajemen Risiko Pembiayaan Murabahah di BMT Amanah Ummah - Endro Wibowo (Al Tijarah, 2015)
This study aims to determine and analyze the process of murabahah financing risk management. Murabahah financing still dominates financing composition in sharia financial institutions, including BMT. BMT considers that murabahah financing process has a small risk so BMT expend more financing to this type. The composition of murabahah financing that is still very large in BMT and the existence of muamalah rules which states that "profit is in return from the readiness to bear losses" causing murabahah financing risk management process since prospective members or members of BMT proposed financing until the repayment of financing installments interesting to investigate. This research uses qualitative approach. Primary data comes from interviews with administrators and managers of BMT, participatory observation, and focus group discussions (FGD) as well as documents related to murabahah financing. Secondary data comes from books, journals, magazines, newspapers, and documents or reports of research activities ever undertaken related to financing in BMT Amanah Ummah. This study concludes that: (1) BMT Amanah Ummah has not conducted risk management process properly because it has not documented risk management process. (2) Risks that are the main focus in murabahah financing in BMT Amanah Ummah are financing risks, namely the risk of failure of prospective members or members of financing in fulfilling the obligation to pay the installment of financing. (3) BMT Amanah Ummah has not applied sharia principles because the transaction contains riba jahiliyyah.